2021
DOI: 10.1111/jphd.12469
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status and behavior in elderly Koreans with periodontal disease

Abstract: Objective The purpose of this study was to investigate oral health status and oral health behaviors in elderly Koreans with periodontal disease. Methods The data of the Seventh Korea National Health and Nutrition Examination Survey (2016–2018) were used. This cross‐sectional study included 2981 individuals who were at least 65 years of age. Periodontal disease was assessed in oral health exams. Subjective oral health status (e.g., toothache) and oral health behaviors (e.g., tooth brushing and oral health exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…And self-reported oral health behaviors mainly included frequency of brushing teeth, brushing methods, usage of floss or mouth wash, frequency of visiting the dentist, the usage of use oral hygiene products, etc. [ 16 , 22 ]. A self-assessed survey on the oral health behaviors of dental and medical students showed that the junior dental students showed highly significant improvement than their counterparts in the items about frequency of brushing teeth, brushing methods of vertical scrub or Bass technique, usage of floss or mouth wash [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…And self-reported oral health behaviors mainly included frequency of brushing teeth, brushing methods, usage of floss or mouth wash, frequency of visiting the dentist, the usage of use oral hygiene products, etc. [ 16 , 22 ]. A self-assessed survey on the oral health behaviors of dental and medical students showed that the junior dental students showed highly significant improvement than their counterparts in the items about frequency of brushing teeth, brushing methods of vertical scrub or Bass technique, usage of floss or mouth wash [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seniors with diabetes have worse physical and immunological function than others, which exacerbates their dental health predicament. It is commonly acknowledged that improving one's oral health state is inextricably linked to excellent oral health behaviors [10]. Preventive oral behaviors such as ossing and brushing teeth have been shown to reduce susceptibility to periodontal disease, dental caries, and tooth loss [11].…”
Section: Introductionmentioning
confidence: 99%